The Relationship Between Serum Interleukin-1α and Asymptomatic Infrarenal Abdominal Aortic Aneurysm Size, Morphology, and Growth Rates. (July 2018) - Ahmad, Mehtab; Kuravi, Sahithi; Hodson, James; Rainger, G. Ed; Nash, Gerard B.; Vohra, Rajiv K.; Bradbury, Andrew W.
Abstract : Objective/Background: In a pilot study, a relationship between abdominal aortic aneurysm (AAA) diameter and serum interleukin (IL)-1α levels was reported, and that endothelial cell (EC) activation in vitro in response to serum from patients with AAA was blocked by anti-IL-1α antibodies. The aim of the present study was to further investigate the relationship between serum IL-1α and asymptomatic infrarenal AAA size, morphology, and growth rates. Methods: Serum IL-1α was measured using enzyme linked immunosorbent assay in 101 patients with asymptomatic, infrarenal AAA and related to aneurysm size, morphology, and growth rates. Results: IL-1α was measured in 101 patients. There was no statistically significant difference in mean age between men and women. IL-1α was detectable in 62.4% of patients; median IL-1α titre was 3.26 pg/mL. There was no statistically significant relationship between IL-1α and maximum AAA antero–posterior diameter as measured by ultrasound ( p  = .649), AAA morphology (aortic length [ p  = .394], sac [ p  = .369], and thrombus volume [ p  = .629]) as measured on computed tomography, absolute increase in AAA diameter ( p  = .214), or AAA growth rate ( p  = .230). Conclusion: IL-1α is detectable in the majority of patients with infrarenal AAA, but the cause and clinical significance of this novel observation remains unknown.